Localization- and mutation-dependent microRNA (miRNA) expression signatures in gastrointestinal stromal tumours (GISTs), with a cluster of co-expressed miRNAs located at 14q32.31 - Haller, Florian; Von Heydebreck, Anja; Zhang, Jitao David; Gunawan, Bastian; Langer, Claus; Ramadori, Giuliano; Wiemann, Stefan; Sahin, Özgür (Journal of Pathology, 2010)
The molecular biology and clinical behaviour of gastrointestinal stromal tumours (GISTs) are associated with their anatomical localization (stomach or intestine), and also with the mutation status of the receptor tyrosine kinases KIT and PDGFRA. Twelve GISTs were evaluated for differential miRNA expression signatures by use of microarrays representing 734 human miRNAs. Thirty-two miRNAs were found to be differentially expressed according to localization and mutation status. Differential expression was further analysed and confirmed for four miRNAs (miR-132, miR-221, miR-222, and miR-504) by qRT-PCR in 49 additional GISTs. Differentially expressed miRNAs were functionally mapped to KIT/PDGFRA signalling and G1/S-phase transition of the cell cycle, revealing 22 predicted miRNA/mRNA interactions for ten gene targets from KIT/PDGFRA signalling, and 12 interactions for 12 gene targets of G1/S-phase transition. Moreover, the expression of 44 miRNAs clustered in a genetically imprinted region at 14q32.31 was found to be strongly correlated in the microarray analysis. This was confirmed for two selected miRNAs (miR-134 and miR-370) from the 14q32.31 cluster by qRT-PCR in 49 additional GISTs, and the expression of these two miRNAs was significantly lower in GISTs with 14q loss, and also in GISTs with tumour progress. miRNA profiling may prove to be a key determinant of the biology and clinical features of GISTs. Copyright © 2009 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
CRIS-Team Scopus Importer:2025-03-24
Keywords: Chromosome 14q; Gastrointestinal stromal tumour; miR-132; miR-221; miR-222; miR-504; miRNA